2012
DOI: 10.4236/fns.2012.33052
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic and Bacteriocin Sensitivity of <i>Listeria monocytogenes</i> Strains Isolated from Different Foods

Abstract: This study aimed to determine the antibiotic and bacteriocin sensitivity of <i>Listeria monocytogenes</i> strains isolated from animal derived foods. With disc diffusion assay, all fourteen L. <i>monocytogenes</i> strains were suscepti-ble to the antibiotics, including penicillin G, vancomycin, tetracycline, chloramphenicol, rifampicin, erythromycin, gentamicin and trime- thoprim. However, the percentages of fosfomycin and streptomycin resistances were 92.9% and 7.1%, respectively. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
5
12
0
Order By: Relevance
“…On the other hand, tetracycline was shown to have good activity against L. monocytogenes in our study. These results are in agreement with those reported previously by Altuntas et al (27) Previous studies have shown that Listeria spp., including L. monocytogenes, are resistant to various antibiotics such as phosphomycin, streptomycin (27), rifampin (18), sulfonamide, tetracycline, ciprofloxacin (21), clindamycin, streptomycin, amikacin (17), tilmicosin, and tetracycline (28). Although most researchers reported that strains of Listeria spp.…”
Section: Discussionsupporting
confidence: 96%
“…On the other hand, tetracycline was shown to have good activity against L. monocytogenes in our study. These results are in agreement with those reported previously by Altuntas et al (27) Previous studies have shown that Listeria spp., including L. monocytogenes, are resistant to various antibiotics such as phosphomycin, streptomycin (27), rifampin (18), sulfonamide, tetracycline, ciprofloxacin (21), clindamycin, streptomycin, amikacin (17), tilmicosin, and tetracycline (28). Although most researchers reported that strains of Listeria spp.…”
Section: Discussionsupporting
confidence: 96%
“…The most important aspect in food hygiene is the ability of the bacteria to survive in a wide range of temperatures and to make biofilms on various environmental surfaces, which serve as natural habitats or reservoirs (Duggan and Phillips, 1998). Listeria monocytogenes wasn't found in Frozen wings of poultry, frozen breast of poultry that totally disagreed with (Reiter et al, 2005) The result of in vitro sensitivity test showed that ,the isolated L.monocytogenes were highly sensitive to Sulphamethoxazole /trimethoprim (100%), so we can use it in its medication (Swaminathan and Gerner-Smidt, 2007),followed by Gentamycin Ceftazidime and Cephazoline (71.4%), followed by Sulphamethoxazole, ceftriaxone (42.8%), weak sensitivity to Penicillin (14.2%), while the isolated strains were resistant to Erythromycin, Ampicillin and Clindamycin and these results came in accordance with those recorded by (Zeinali et al, 2017) and disagreed with (Altuntas et al,2012). All L.monocytogenes isolates were positive to CAMP test and showed narrow zone of β-heamolysis in sheep agar, the similar results were reported by (Marrouf et al ., 2007).…”
Section: Discussion:-supporting
confidence: 79%
“…to chloramphenicol (Table 2) could be due to the illegal use of this antimicrobial in some poultry farms. The high sensitivity of L. monocytogenes to some antimicrobials commonly used to treat listeriosis (rifampin, trimethoprim/sulfamethoxazole, gentamycin, erythromycin and vancomycin) is in agreement with the reports of Alonso-Hernando et al (2012), Altuntas et al (2012) and Pesavento et al (2010).…”
Section: Antimicrobial Resistance Of Listeria Spp Isolatessupporting
confidence: 84%